2014
DOI: 10.3201/eid2002.131463
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Systemic Morbillivirus Infection in Bottlenose Dolphin, Canary Islands, Spain

Abstract: A systemic morbillivirus infection was diagnosed postmortem in a juvenile bottlenose dolphin stranded in the eastern North Atlantic Ocean in 2005. Sequence analysis of a conserved fragment of the morbillivirus phosphoprotein gene indicated that the virus is closely related to dolphin morbillivirus recently reported in striped dolphins in the Mediterranean Sea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 13 publications
1
26
0
Order By: Relevance
“…The information presented here increases the number of morbillivirus-positive cases within the Canarian Archipelago from two (56,57) to eight cases. Regarding HV, the phylogenetic analysis performed in the current study provides valuable information about a possible pathogenic branch of alphaherpesviruses in cetaceans that might be responsible for some fatal cases worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…The information presented here increases the number of morbillivirus-positive cases within the Canarian Archipelago from two (56,57) to eight cases. Regarding HV, the phylogenetic analysis performed in the current study provides valuable information about a possible pathogenic branch of alphaherpesviruses in cetaceans that might be responsible for some fatal cases worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Dolphins and seals are vulnerable to viral infection, with serious pandemics of influenza virus (Cox and Subbarao, 2000;Groth et al, 2014), poxvirus (Fiorito et al, 2015) and morbillivirus (Sierra et al, 2014(Sierra et al, , 2016. Although no pandemics have been reported for large whales, as right whales undertake large scale migrations they could be the source of, and vectors for, potentially serious zoonoses (Bogomolni et al, 2008).…”
Section: Methods For Assessing Factors Affecting Right Whale Healthmentioning
confidence: 99%
“…Immunohistochemistry (IHC) has greatly enhanced the sensitivity and specificity of histopathological diagnosis by enabling the detection of morbillivirus antigen in cases where tissue preservation is poor or where classical lesions have been obscured by opportunistic pathogens. IHC studies have been conducted by using a commercially available MoAb for CDV N protein [ 5 , 6 , 7 , 33 , 66 , 67 , 68 , 69 ], a MoAb for PDV hemagglutinin [ 2 , 53 , 57 ], or a rabbit polyclonal antiserum to rinderpest virus [ 70 ]. Together with RT-PCR, these techniques recently permitted the identification of morbillivirus outbreaks in T. truncatus and T. aduncus from South Australia in 2013 [ 51 ], and in T. truncatus from the NW Atlantic, ongoing since 2013 [ 71 ].…”
Section: Diagnosismentioning
confidence: 99%
“…In addition, an IHC and RT-PCR retrospective survey showed that DMV caused chronic CNS disease in S. coeruleoalba and D. delphis washed ashore in the Canary Islands in the period 2002-2011 [ 33 ]. Finally, a systemic DMV infection was observed in a T. truncatus stranded in Lanzarote, Canary Islands, in 2005 [ 69 ]. Thus, at least two strains of CeMV are circulating in cetaceans from this ocean province.…”
Section: Outbreaks Of Disease and Epidemiologymentioning
confidence: 99%